Determinación del nivel óptimo de fibra en raciones de crecimiento de pollo de carne - Cango Zhingre, Erika Stefanía (2021)
This research evaluated the productive performance of broilers with the incorporation of increasing levels of fibre in their diet, raised in the canton of Paltas, province of Loja. A completely randomised design was applied, with 203 broilers of the Cobb 500 genetic line, one day old, unsexed; which were distributed in 3 treatments, with 10 experimental units, consisting of 7 and 6 animals. Treatment 1 consisted of providing fibre at 3 %, in treatment 2 fibre was applied at 4 % and in treatment 3 fibre was provided at 5 %. The results showed significant differences (P = < 0.0001) in final weight between treatments; thus, it was evident that treatment 2 obtained better results in average daily intake and feed conversion, over the other treatments. With regard to the digestive parameters, data was collected by slaughtering 8 chickens of each treatment on day 28, thus obtaining results that showed significant differences between treatments. Therefore, it is concluded that treatment 2 was the most effective in terms of productive parameters and treatment 3 was the most effective in terms of digestive organ weights. Key words: Fibre, productive parameters, digestive parameters, broiler chicken, treatment